Long term survivors of Glioblastoma : Clinical and radiological profile of a portuguese cohort - João Pedro Borges Catela dos Reis Sousa (2021)
Purpose: Glioblastoma (GBM) is the most common primary malignant brain tumor and entails a grim prognosis. The aim of the present study is to provide an in-depth analysis of clinical, analytical and radiological features of a cohort of GBM long-term survivors (LTS) treated at a major tertiary referral Hospital in Portugal and perform a matched cohort comparison to patients surviving less than 2 years in order to identify distinctive prognostic factors. Methods: A study population was identified by analyzing a pathological database of GBM patients operated between 2010 and 2018 at Centro Hospitalar Universitário São João. LTS were identified if they had an overall survival (OS) of at least 36 months. A matching cohort for age, gender and performance status with less than 24 months OS was identified through binary logistic regression. Clinical and radiological data were obtained and statistically significant differences identified. Results: Out of 436 adult GBM patients, 27 met inclusion criteria. Tumor's mass effect was identified more often in the matched cohort versus the LTS cohort (p=0.006), subventricular proximity was significantly different between cohorts, with subventricular zone involvement (group I/II) more frequent in the matched cohort (p=0.039). Neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) were significantly lower in the LTS cohort compared to the matched cohort (p < 0.001). Conclusions: In our group of GBM long-term survivors, the absence of mass effect, low serum inflammatory markers and low frequency of subventricular zone involvement stand out as variables with prognostic impact when compared to non-long-term survivors.